The Effectiveness of Implementation of the MGMP Revitalization Program as a Media Increasing English Teacher Competency in Pidie District - Ramlan Ramlan; Farizawati Farizawati; Saddam Hasrul (Budapest International Research and Critics University, 2020)
This research was conducted to determine the effectiveness of the revitalization program for Musyawarah Guru Mata Pelajaran Teacher's Deliberation of Course of Study (MGMP) as a medium to improve English teacher competency. The objectives of this study are (1) Analyzing the reaction of each participant to the English Subject Teacher Consultation activity in Pidie District. (2) Explain knowledge and skills regarding the theoretical and philosophical foundations of English subjects after participating in the English Subject Teacher Consultation activities in the Pidie District. (3) Analyze the motivation of each participant in the English Subject Teacher Meeting to transfer knowledge and skills into the English learning process. (4) Analyzing the impact of the activities of the English Subject Teachers Conference on the development of English teacher competencies in Pidie District. The research method applied in this study is evaluative research based on (Arikunto 2007: 222) evaluative research can be interpreted as a process carried out in order to determine policy by first considering the positive values and benefits of a program, as well as considering the processes and techniques that have been used to do a research. The results showed that each participant's positive reaction to the implementation of the program could significantly influence the increase in knowledge and skills for each participant / program participant in relation to the philosophical and theoretical basis of learning English in secondary schools. However, increasing knowledge and skills did not always have an impact significant at the practical level, namely the quality of the learning process carried out by teachers, participants in the MGMP revitalization program, in the classroom. Teachers still tend to use conventional patterns in the process of learning English. . In general, the implementation of the MGMP revitalization program has been able to improve the participants' knowledge and skills discourse on the philosophical and theoretical foundations of English learning. The obstacle that arises then is the lack of motivation of some participants to apply knowledge and skills in the context of their performance. The lack of motivation to apply this knowledge and skills has resulted in learning practices that have not changed much. This shows that the forum has not been able to effectively and optimally carry out its role and function as a means for the development and development of teaching professionalism.